PSYCHOLOGICAL DISTRESS IN INDIA DUE TO LOCKDOWN DURING COVID -19 PANDEMIC (Journal of Forensic Medicine & Toxicology, 2020)
The ongoing pandemic COVID-19 has egregiously contrived the humankind and brought the world on its knees. Despite vigorous manoeuvre to check the transmission, the gigantic upsurge is seen in the number of infected cases and fatalities every day. In January 2020, this viral outbreak was declared to be a Public Health Emergency by the World Health Organisation which later in March asserted to be pandemic (WHO, 2020). This pandemic has compelled mankind to pause their personal and professional affairs and sojourn in lockdown. Governments around the globe have to ratify this step and impose stringently on the citizens. These austere quarantine initiatives and policies have precipitated psychological and emotional anguish among individuals. The society perceives the requisite of lockdown, despite owing to psychological distress is ineffectual in maintaining it credibly.
Keywords: partook; restaurants; workout